A mini-review on the application of computational strategies in multi-armed star-PEG Polymeric micelles for drug delivery - Mat Udin, Syarah; Maarof, Hasmerya; Abdul Rahman, Norizah (John Wiley and Sons, 2023)
Polymeric micelles (PM) are amphiphilic block copolymers that can form nanoscopic core/shell structures, making them highly effective for drug delivery systems (DDS). Multi-armed starshaped poly(ethylene glycol) (PEG) polymers, a promising type of PM, provide a regulated release of drugs and can be integrated with numerous endpoints to create multifunctional drug delivery systems capable of transporting a large number of drugs. Star-PEG polymers can also be cross-linked to create three dimensional hydrogels with variable functionalities and sizes, increasing blood flow and reducing unanticipated drug release. In this review, we present state-of-the-art computational tools for analyzing drug pharmacokinetic profiles and identifying molecular interactions critical for successful drug encapsulation in star-PEG PM. By taking into account the features described, academic and industrial researchers can identify novel interrelationships in PM and maximize their capabilities as DDSs for systemic administration, ultimately enhancing the medicinal qualities of drug delivery.